(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
Translating political texts from English into Uzbek presents unique challenges that arise from linguistic, cultural, and ideological differences. Political discourse is characterized by nuanced terminology, persuasive rhetoric, and culturally specific references, which often complicate accurate and effective translation. This study examines the primary problems encountered in translating political texts, such as lexical gaps, cultural untranslatability, and the preservation of ideological intent. Using qualitative analysis of selected political speeches and documents, the research highlights strategies employed by translators to negotiate these difficulties and maintain the text’s original impact. The findings underscore the importance of contextual awareness and interdisciplinary expertise in political translation.